Study of charmonium decays to K0SKπ in the B → (K0SKπ)K channels - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Physical review, 2023)
A study of the B+→K0SK+K−π+ and B+→K0SK+K+π− decays is performed using proton-proton collisions at center-of-mass energies of 7, 8 and 13 TeV at the LHCb experiment. The K0SKπ invariant mass spectra from both decay modes reveal a rich content of charmonium resonances. New precise measurements of the ηc and ηc(2S) resonance parameters are performed and branching fraction measurements are obtained for B+ decays to ηc, J/ψ, ηc(2S) and χc1 resonances. In particular, the first observation and branching fraction measurement of B+→χc0K0π+ is reported as well as first measurements of the B+→K0K+K−π+ and B+→K0K+K+π− branching fractions. Dalitz plot analyses of ηc→K0SKπ and ηc(2S)→K0SKπ decays are performed. A new measurement of the amplitude and phase of the Kπ S-wave as functions of the Kπ mass is performed, together with measurements of the K∗0(1430), K∗0(1950) and a0(1700) parameters. Finally, the branching fractions of χc1 decays to K∗ resonances are also measured.